2023
DOI: 10.1590/acb382223
|View full text |Cite
|
Sign up to set email alerts
|

Columbianadin attenuates doxorubicin-induced cardiac injury, oxidative stress, and apoptosis via Sirt1/FOXO1 signaling pathway

Bo Peng,
Li Rao,
Jiaolong Yang
et al.

Abstract: Purpose: Oxidative stress and apoptosis contribute to the pathological basis of doxorubicin (DOX)-induced cardiotoxicity. Columbianadin (CBN) is one of the main bioactive constituents isolated from the root of Angelica pubescens . Herein, we intended to explore the potential role and molecular basis of CBN in DOX-induced cardiotoxicity. Methods: C57BL/6 mice were subjected to DOX (15 mg/kg/day, i.p.) to generate DOX-induced cardiotoxicity. CBN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…It is well known that ROS can cause membrane damage and mitochondrial dysfunction, leading to cell apoptosis. Recent studies also identified some molecular targets involved in DOXO-induced oxidative damage and confirmed the beneficial effects of antioxidant compounds in alleviating cardiotoxicity [56][57][58].…”
Section: Discussionmentioning
confidence: 71%
“…It is well known that ROS can cause membrane damage and mitochondrial dysfunction, leading to cell apoptosis. Recent studies also identified some molecular targets involved in DOXO-induced oxidative damage and confirmed the beneficial effects of antioxidant compounds in alleviating cardiotoxicity [56][57][58].…”
Section: Discussionmentioning
confidence: 71%